Vitamin A Concentration in Cord and Maternal Serum and its Relation to Birth Weight (Ibrahim Medical College Journal, 2009)
Low birth weight (LBW) is a common problem in Bangladesh associated with poor survival, growth and development. Among many factors, Vitamin A deficiency is thought to be associated with LBW. To investigate this relation a study was conducted at Maternity and Child Health Training Institute at Azimpur, Dhaka during January 2000 - July 2002. One hundred pregnant women (38-40 wks of gestation) with their newborns were included. Weights of the newborns were recorded within 20 - 30 minutes of delivery. Vitamin A level was estimated in maternal and cord serum. The newborns having weight